The pyramidalis–anterior pubic ligament–adductor longus complex (PLAC) and its role with adductor injuries: a new anatomical concept - Schilders, Ernest (Knee Surg Sports Traumatol Arthrosc, 2017)
PURPOSE: Adductor longus injuries are complex. The conflict between views in the recent literature and various nineteenth-century anatomy books regarding symphyseal and perisymphyseal anatomy can lead to difficulties in MRI interpretation and treatment decisions. The aim of the study is to systematically investigate the pyramidalis muscle and its anatomical connections with adductor longus and rectus abdominis, to elucidate injury patterns occurring with adductor avulsions. METHODS: A layered dissection of the soft tissues of the anterior symphyseal area was performed on seven fresh-frozen male cadavers. The dimensions of the pyramidalis muscle were measured and anatomical connections with adductor longus, rectus abdominis and aponeuroses examined. RESULTS: The pyramidalis is the only abdominal muscle anterior to the pubic bone and was found bilaterally in all specimens. It arises from the pubic crest and anterior pubic ligament and attaches to the linea alba on the medial border. The proximal adductor longus attaches to the pubic crest and anterior pubic ligament. The anterior pubic ligament is also a fascial anchor point connecting the lower anterior abdominal aponeurosis and fascia lata. The rectus abdominis, however, is not attached to the adductor longus; its lateral tendon attaches to the cranial border of the pubis; and its slender internal tendon attaches inferiorly to the symphysis with fascia lata and gracilis. CONCLUSION: The study demonstrates a strong direct connection between the pyramidalis muscle and adductor longus tendon via the anterior pubic ligament, and it introduces the new anatomical concept of the pyramidalis–anterior pubic ligament–adductor longus complex (PLAC). Knowledge of these anatomical relationships should be employed to aid in image interpretation and treatment planning with proximal adductor avulsions. In particular, MRI imaging should be employed for all proximal adductor longus avulsions to assess the integrity of the PLAC.